Morphological and Anatomical Identification of Rhizoctonia Mycorrhaza From Four Species of Phalaenopsis sp.: Morphological and Anatomical Identification of Rhizoctonia Mycorrhaza From Four Species of Phalaenopsis sp. - R. Soelistijono; Annissa Tiara Maharani; Daryanti; Endang Suprapti (JURNAL ILMIAH AGRINECA, 2026)
Rhizoctonia mycorrhiza is an endophytic fungus that plays an important role in orchid growth and can increase plant resistance to environmental stress and pathogens. The purpose of this study was to examine the morphology and anatomy of Rhizoctonia mycorrhiza isolated from four Phalaenopsis orchid species. The study used a quantitative descriptive method through direct observation and analysis of the percentage of hyphal cell nuclei. The results showed that the four Rhizoctonia mycorrhiza isolates had different colony morphological characteristics. Isolates from Phalaenopsis venosa had brownish-white colonies with rapid mycelial growth, isolates from Phalaenopsis amabilis showed grayish-white colonies with thinner growth and Phalaenopsis celebensis, colonies were white-brown and began to form dark masses suspected to be sclerotia. Meanwhile, isolates from Phalaenopsis gigantea showed white-dark green colonies with a circular growth pattern and rapid spread. Anatomical observations showed that all isolates had the typical characteristics of Rhizoctonia, namely hyphal branching at a 90° angle, septate hyphae, and the presence of more than one cell nucleus. Based on the count of 120 hyphal cells, isolates from P. venosa (63.3%), P. amabilis (66.6%), and P. gigantea (60%) were dominated by binucleate cells, while isolates from P. celebensis (70%) were dominated by multinucleate cells. This indicates the physiological diversity of Rhizoctonia mycorrhiza among orchid species. Thus, this study confirms that the roots of four species of Phalaenopsis orchid species contain Rhizoctonia mycorrhiza with morphological and anatomical variations that can be used as an inoculum source for the development of orchid cultivation as well as further research related to its physiological function and application as a biological agent.